Global coral bleaching event detection from satellite monitoring of extreme heat stress - Little, Christine M.; Liu, Gang; De La Cour, Jacqueline L.; Eakin, C. Mark; Manzello, Derek; Heron, Scott F. (Frontiers in Marine Science, 2022)
Over the past four decades, coral bleaching events have occurred with increasing frequency and severity, directly linked to increasing ocean temperature due to climate change. For the latter half of that period, satellite monitoring by NOAA Coral Reef Watch in near real-time has provided invaluable insight into bleaching risk. Here, we describe a novel application of those products to develop basin-scale tools for tracking the development of extreme heat events that enable monitoring of global coral bleaching events. Case studies of historical extreme events (1982-2018) across the three tropical ocean basins (Indian, Pacific and Atlantic) were analysed using this basin-scale approach to identify key thresholds of heat stress extent for the definition of global bleaching. Global- scale events are apparent when all three tropical basins experience heat stress in at least 10% of reef- containing locations. An 8-month ‘detection window’ was determined as the optimal period of time through which pixels exposed to heat stress should continue to be counted as part of a basin-scale event to account for seasonal variations across ocean basins. Understanding the broader context of basin-scale conditions can inform management of individual reefs, manager networks and other reef stakeholders. Operationalising this product for near real-time delivery will provide an effective communication of the status of coral reefs around the world during an era of unprecedented climate threats.